Densely homogeneous fuzzy spaces - Samer Al Ghour (International Journal of Electrical and Computer Engineering (IJECE), 2019)
We extend the concept of being densely homogeneous to include fuzzy topological spaces. We prove that our extension is a good extension in the sense of Lowen. We prove that a-cut topological space (X,I_a) of a DH fuzzy topological space (X,I) is DH in general only for a=0.